PENINGKATAN KUALITAS LAYANAN REFERENSI PERPUSTAKAAN POLITEKNIK NEGERI PONTIANAK - Sari, Indah Permata; Latifa Hanum, Atiqa Nur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research discussed about the quality improvement of reference service of Pontianak state polytechnic library.The aims of this researchwere to find out the efforts ofthe improvement of service quality and the obstacles. The method used was qualitative with a descriptive approach that could be used as a guide so that the focus of the research was in accordance with the facts. The data collections were done by observation, interview and documentation. Conducted by researchers on informants, namely the first librarians and visitors who came to Pontianak state polytechnic library.The result showed that the quality improvementof reference service was still not carried out, starting from obstacles such as small rooms, book shelves that are not neatly arranged and even the collection material available in the reference service is very dirty,dusty, event most yellowing, and there are no guards or staff who maintain the reference service room, the with an increase the quality of this service can provide comform felt b users and make it easier for users to find the source of information needed to reference service. because it still had to be addressed starting from a room that was still very limited so that it became an obstacle in improving the quality of reference services.Keywords: Polnep Library, reference serviceÂ